Finite absolute continuity of Gaussian measures on infinite-dimensional spaces - Ryabov, G. V. (Ukrains’kyi Matematychnyi Zhurnal, 2008)
We study the notion of finite absolute continuity for measures on infinite-dimensional spaces. For Gaussian product measures on \(R^∞\) and Gaussian measures on a Hilbert space, we establish criteria for finite absolute continuity. We consider cases where the condition of finite absolute continuity of Gaussian measures is equivalent to the condition of their equivalence.